2013
DOI: 10.1162/jocn_a_00442
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond Inferior Prefrontal Involvement in Semantic Control: Evidence for the Additional Contribution of Dorsal Angular Gyrus and Posterior Middle Temporal Cortex

Abstract: Abstract■ Semantic cognition requires a combination of semantic representations and executive control processes to direct activation in a task-and time-appropriate fashion [Jefferies, E., & Lambon Ralph, M. A. Semantic impairment in stroke aphasia versus semantic dementia: A case-series comparison. Brain, 129, 2132Brain, 129, -2147Brain, 129, , 2006. We undertook a formal meta-analysis to investigate which regions within the large-scale semantic network are specifically associated with the executive compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

70
673
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(779 citation statements)
references
References 154 publications
70
673
2
4
Order By: Relevance
“…It is noteworthy to mention that the peak of the locus of difference of activation in the left posterior middle temporal gyrus found in our study is posterior to the one reported in previous semantic studies in young adults (Noonan, Jefferies, Visser, & Lambon Ralph, 2013). In addition, patterns of cortical activation in older subjects were more widely distributed across both hemispheres than in younger subjects.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It is noteworthy to mention that the peak of the locus of difference of activation in the left posterior middle temporal gyrus found in our study is posterior to the one reported in previous semantic studies in young adults (Noonan, Jefferies, Visser, & Lambon Ralph, 2013). In addition, patterns of cortical activation in older subjects were more widely distributed across both hemispheres than in younger subjects.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, Davis et al (2008) and Huang et al (2012) postulated that compensatory neural mechanisms in older adults occur not only in prefrontal regions but also in posterior regions, such as the temporoparietal region, which is less affected by normal aging than prefrontal regions . Along this line, age-related differences may be observed in other cerebral region, such as the posterior middle temporal gyrus, that undertakes the same cognitive process than IPC and might play a more critical role in a comprehensive semantic judgment task (Noonan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left posterior middle temporal gyrus has also been identified as an important region of the semantic network (Whitney et al, 2012;Jefferies, 2013;Noonan et al, 2013). More specifically, it has been recently suggested that this region plays a major role in the executive aspects of semantic cognition, including the manipulation and selection of task relevant knowledge as well as the inhibition of task-irrelevant knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The left angular gyrus is known to play a role in semantic processing (Seghier, Fagan, & Price, 2010), and in executively demanding semantic tasks (Noonan, Jefferies, Visser, & Lambon Ralph, 2013). It has also been found to be implicated in subliminal semantic priming (Diaz & McCarthy, 2007), and in relatedness judgements when word pairs are semantically related compared to when they are unrelated (Chou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%